Bithalamic infarct causing acute consciousness disturbance. Early diagnosis with diffusion-weighted MRI - Weise, J; Krapf, H; Küker, W (2001)
Fast diagnostic evaluation of somnolent or unconscious patients is a demanding task for neurologists. Apart from postictal, metabolic, and toxic causes, vascular syndromes must be rapidly identified in order to initiate a specific fibrinolytic therapy. Given its high mortality if not treated in time, this dictum holds especially true for basilar artery occlusion. However, certain ischemic lesions in the vascular territory of the basilar artery without occlusion of the basilar artery itself can also result in somnolence, sopor, or even unconsciousness. Here we report early imaging signs of bithalamic infarctions as the cause of acute sopor using diffusion-weighted (DW)-MRI, which reliably identifies acute bithalamic infarctions as a possible cause of acute consciousness disturbance, even with noncooperative patients.